“A loyal friend, even when storms descend” An Analysis of Students’ Critical Views on Media Development through their Poems - Kasprabowo, Teguh; Rahayu, Endang; Rustipa, Katharina; Yulistiyanti, Yulistiyanti (Universitas Negeri Semarang, 2024)
The study aims to explore students’ critical views on the development of media, especially television and radio, through their poems. The respondents were 17 students attending Introduction to Pop Culture course. Utilizing Hanauer’s meaningful literacy concept (2012) this qualitative case study investigated respondents’ perceptions towards media development and its impacts. Major themes found in the study showed that students expressed (1) nostalgia with the media (2) critical views of the content of the media (3) Media as the source of comfort and connection (4) disillusionment with the media, and (5) media evolution and its impact. This study also highlighted the possibilities of integrating literature, especially poem, in the language classrooms in the context of English as a Foreign Language (EFL) to encourage students’ critical thinking.